Evidence‐based practice guideline on integrative medicine for stroke 2019. Issue 2 (22nd May 2020) - Ni, Xiaojia; Lin, Hao; Li, Hui; Liao, Wenjing; Luo, Xufei; Wu, Darong; Chen, Yaolong; Cai, Yefeng; ,
Abstract: Objective: Stroke is the leading cause of death and disability in China. Chinese medicine integrated with conventional medicine is now widely used in the prevention and treatment of stroke. A clinical practice guideline for the application of integrative medicine in stroke is urgently needed. Methods: This guideline was developed following the methodology and procedures recommended in the World Health Organization Handbook for Guideline Development and the Guideline Development Handbook for Diagnosis and Therapy of Integrative Medicine. The quality of evidence and strength of recommendations were evaluated using the GRADE approach. The guideline followed the RIGHT statement and AGREE II was consulted to ensure its quality. Results: A multidisciplinary working team was established. Eleven research questions from 15 clinical questions were identified by questionnaire surveys, face‐to‐face meetings, and analyzed by the working team. Fourteen recommendations regarding integrative medicine for ischemic stroke, hemorrhagic stroke, and complications of stroke were formulated from systematic reviews of the benefits, harms, cost‐effectiveness, quality of evidence, the values and preferences of patients and their family members, feedback on proposed recommendations from medical practitioners from a variety of disciplines, and a face‐to‐face consensus meeting. Conclusions: This guideline focuses on clinical treatments that are specific to integrative medicine for stroke and can be used at all levels in medical institutions and rehabilitation facilities. The end‐users of the guideline are most likely to be medical practitioners, including Chinese herbal medicine specialists, acupuncturists, integrative medicine practitioners, physicians, physical therapists, and clinical pharmacists.